(untitled) (Indonesian Minority Justice Review, 2024)
This paper investigates the challenges and opportunities for ensuring equal representation of minority groups in Indonesia’s electoral system. Despite Indonesia’s democratic framework, minority groups—whether ethnic, religious, or socio-economic—often face barriers to full participation in political processes, including voting rights, representation, and access to candidacy. The study analyzes Indonesia’s electoral laws, including the 1999 Election Law and the 2008 Regional Election Law, to assess their impact on minority participation. Through legal analysis, interviews with political analysts, and surveys of minority voters, the paper highlights systemic issues such as voter intimidation, lack of access to information, and underrepresentation of minority groups in legislative bodies. The findings indicate that while the electoral system has made strides in promoting democratic participation, significant disparities remain in the political empowerment of marginalized groups. The paper concludes by recommending legal reforms aimed at increasing minority representation, such as proportional representation, stronger anti-discrimination measures, and policies that encourage political parties to field more candidates from minority backgrounds.